Redefining Employee Commitment: The Role of Digital Work Flexibility and Work-Life Balance in Enhancing Public Service Efficiency - Gunawan, Edi; Mujanah, Siti; Fianto, Achmad Yanu Alif (International Journal of Economics (IJEC), 2025)
This study investigates the effect of digital work flexibility and work-life balance on employee commitment and its impact on public service efficiency at the Regional Revenue Agency (Bapenda) of Surabaya City. Using a quantitative approach with a cross-sectional design, data were collected from 115 civil servants through a structured questionnaire. Data analysis was performed using regression and mediation tests via Python-based statistical tools. The results indicate that both digital work flexibility and work-life balance significantly influence employee commitment. Furthermore, employee commitment fully mediates the relationship between the two independent variables and public service efficiency. This means that any improvements in work flexibility and balance will only lead to enhanced service performance if they are able to foster stronger employee commitment. The study highlights the importance of adaptive and human-centered work arrangements in improving service delivery in public sector institutions. These findings have practical implications for the design of flexible work policies and underscore the strategic role of psychological commitment in the effectiveness of digital transformation in public administration.